Ship London muster book, 1790-1791 (Records of the National Archives. ADM 36/10923.)
Muster table covering 11 May 1790-24 September 1791 of His Majesty's Ship, the London, originally launched 1766, "broken up" 1811, and captained by G. B. Westcott, 1790-1791--information from resource, The National Archives (Great Britain), and from Wikipedia entries for HMS London (1766) and George Blagdon Westcott (viewed Nov. 1, 2017)